Effect Of Tuna Flour Addition On Physical, Chemical, And Organoleptic Properties Of Crackers Physical, Chemical, And Organoleptic Properties Of Crackers - Triyudhani, Isya Lestari; Nalawati, Ara Nugrahayu; Setiawan, Andika Putra (International Applied Science, 2024)
Crackers available in the market only provide a small portion of daily protein needs. Tuna (Euthynnus affinis) belongs to the Scombridae class and is an important commodity in Indonesia. The high nutritional value of tuna fish includes a considerable amount of protein, ranging from 22.6-26.2 g/100 grams of meat. Of the various ingredients that can be added to increase the protein content of crackers, one option is to use tuna flour due to its high protein content. This study aims to identify the optimal ratio and drying period for certain chemical properties as well as considering color, aroma and taste preferences by panelists as well as the shelf life of popular tuna crackers. The parameters used in this study include moisture content, ash content, fat content, protein content which measures the nutritional value; pH which indicates the level of acidity; swelling strength as an indication of textural quality along with organoleptic tests (taste, color, aroma and overall preference) which enables sensory evaluation analysis. The results showed that crackers with the addition of tuna flour have met the quality requirements of SNI 2973-2018. The tuna flour crackers formulation has a moisture content of 0.4%, ash content of 0.2%, protein content of 7.11%, fat content of 16%, pH of 6.48-6.50 and expandability of 0.6%.